Growth of Bifidobacterium species is inhibited by free fatty acids and bile salts but not by glycerides. - Pérez-Burillo, Sergio; Rajakaruna, Sumudu; Paliy, Oleg (AIMS Press, 2022)
High-fat diets have been associated with lower gut and fecal abundances of genus Bifidobacterium. Here, we investigated whether commonly consumed dietary free fatty acids have any detrimental effect on the growth of B. adolescentis, B. bifidum, and B. longum. We found that the presence of free fatty acids in the medium inhibits the growth of Bifidobacterium species to a varying degree, with capric (C10:0), oleic (C18:1), and linoleic (C18:2) acids displaying the largest effect. In comparison, free fatty acids did not affect the growth of Escherichia coli. When fats were added as a mixture of mono- and diacylglycerols, the inhibitory effect on Bifidobacterium growth was abolished.
Keywords: Bacterias gram positivas; Ácidos grasos; Lípidos; Glicéridos; Acidos biliares; Bifidobacterium; Fats; Bile salts; Fatty acids; Glycerides